The Dialogue Method in Small Groups and Its Impact on The Achievement of Primary School Students From the teachers’ point of view in schools in northern Palestine - Ghalia, Nadia Hassan; Darawsheh, Ahlam Mahmood; Alrashdan, Hanadi Sodqi (Journal of Educational and Psychological Sciences, 2022)
This study aimed to identify the effect of the dialogue method in small groups on the achievement of primary school students. The study targeted a community of primary school teachers in northern Palestine, and the sample includes approximately (70-100) male and female teachers, whom are selected according to the available sample. The data has been processed using the Statistical Package for Social Sciences (SPSS), where the tests included descriptive statistics; t-test for independent samples, one way Anova test, simple linear regression test and Cronbach’s alpha coefficient. In order to achieve the objectives of the research, the researchers have used the descriptive survey method by adopting the form as a data collection tool, whereas the form will consist of; a consent to participate in the study, demographic data of the participants, as well as the questionnaire’s paragraphs and fields, which will be evaluated according to the five-point Likert scale. The study resulted to the presence of statistically significant differences between the averages of students’ achievement; The use of the small group dialogue method has a positive effect in teaching, which may show the presence of differences between students in their academic achievement.